Pengembangan Bahan Ajar Buku Cerita Berbasis Discovery Learning Pada Materi IPA Konsep Perpindahan Panas Di Kelas V Sekolah Dasar - Desi Rusinta; Daimun Hambali; Endang Widi Winarni (Universitas Bengkulu, 2020)
The objectives of this research are: 1) describing storybook teaching materials based on discovery learning: 2) describing the feasibility of discovery learning storybook based teaching materials; 3) describe the attractiveness of discovery learning textbooks on natural science concepts of heat transfer in class V of elementary school. The design of this research is research and development with qualitative and quantitative methods. There are five stages in the development of this teaching material product, namely: 1) research and information collecting; 2) planning: 3) develop preliminary product forms: 4) preliminary field testing: 5) play product revision. The limited trial research was conducted in class V SDN 8 Kepahiang. The research instrument used was a questionnaire validation of teaching materials and student questionnaire responses. Data collection techniques are interviews, observation, and questionnaires. The research data were analyzed qualitatively and quantitatively. The results obtained are: 1) the development of teaching materials using Borg And Gall steps conducted by researchers up to the fifth stage: 2) The validation results from 9 expert validators, each of 3 validators for 3 aspects, namely: material, language, and design states teaching materials are suitable for use in grade V elementary school; 3) The attractiveness aspect based on 10 students the results are very good with a detailed percentage of 88.57% of students responding positively to the material aspects, 100% of students respond positively to the teaching material aspects of language, and 100% of students respond positively to the teaching material aspects of the attractiveness of teaching materials.